Literary translators' associations and the construction of translation as literature in Spain - Juan Carmona-Zabala (Cadernos de Tradução)
In this article I approach literary translators’ associations in the context of late twentieth century Spain through the theoretical lens of Bourdieu’s sociology of literature. I argue that one important function of the activism that these organizations promoted was the social construction of literary translation as a form of literature in its own right. In this article I present multiple instances of how translators made use of the communicative spaces that their associations created (round tables, publications, conferences, interviews, etc.) to publicly represent translation as a kind of creation which can be largely autonomous from economic as well as scholarly considerations, and which presents three traits that are specific to literature. These traits are self-referentiality, ability to create its own object, and a structure defined by a heteronomous and an autonomous pole. This sociological approach to a largely understudied dimension of translators’ collective action invites us to revise the notion that literary translators’ associations function as professional bodies that, for the most part, fail to protect the interests of their members.